Sino orbital mucormycosis treated with fluconazole - Alebachew, Assaye N.; Dibaba, Dawit K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
The successful treatment of mucormycosis requires; early diagnosis; reversal of underlying predisposing risk factors, if possible, surgical debridement, where applicable and prompt antifungal therapy. Amphotericin B is the gold standard antifungal treatment against mucormycosis to date. However, there are newer agents described recently like posaconazole and isavuconazole which can be used as an option in a few instances. Although amphotericin B especially the liposomal preparation is the preferred agent, the availability and the cost limit its use, especially in resource-limited setups. Generally, azole drugs, especially the first generations such as fluconazole, are not effective against zygomycetes. However, few reports showed complete recovery after use of fluconazole for adjunct treatment. Here we report on a 35-year-old newly diagnosed diabetic woman with Sinoorbital mucormycosis who has been treated with surgical debridement and intermittent bases of amphotericin B and was discharged home without optimal response but returned completely improved after three months of oral fluconazole.